Hold on for beer life ebook A sloan krause mystery (#5.5). - Alexander, Ellie (A Sloan Krause Mystery, 2022)
Amateur sleuth and craft brewer Sloan Krause returns in Hold on for Beer Life, a new cozy mystery novella from author Ellie Alexander. Includes recipes! Spring has given way to early summer in the Bavarian village of Leavenworth, Washington, where Sloan Krause and her brewing partner in crime, Garrett Strong, are taking off for a weekend adventure. They've been invited to Confluence Brewing in nearby Wenatchee for the brewery's soft opening. Confluence is taking beer tourism to the next level with farm-to-table dinners in their lush apple orchard, hop field tours, overnight accommodations complete with beer-themed breakfasts, and of course, plenty of tastings. The trip is part work and part pleasure. Sloan is looking forward to a weekend away with Garrett and getting a chance to learn more about Confluence. There's no doubt that the nanobrewery is a perfect escape for any craft beer lover. Sloan is immediately captivated by the rustic barn, turned tasting room, and the expansive orchards that stretch as far as her eye can see. Dinner under the stars is nothing short of magical. Maybe it's the organic food and beer pairings, or perhaps it's the company. Either way, she's happy to be finally stepping outside of herself and figuring out what's next for her. However, the blissful moment is short-lived. Sinister things are brewing at Confluence. When Sloan discovers one of the brewery's young interns knocked out in the middle of the orchard, she realizes she and Garrett are in for more than sampling summer IPAs. If they can't get to the bottom of what's really going on at the new start-up, they might just end up at the bottom of the barrel.